Enterprise-wide Service-Oriented Architecture Initiative with Information Quality for Agility in Services Environment - Sulong, Muhammad Suhaizan; Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing (Publications International, 2013)
An enterprise transitioning to service-oriented architecture by having an enterprise-wide initiative leads to a complete enterprise architecture in the services environment. Although service-oriented architecture offers great potential for making enterprises more agile in a highly competitive and fast changing business environment, applying an appropriate information quality management in the initiative, the enterprise can better increase agility in their services environment. This paper addresses the enterprise needs of service-oriented architecture team, considering the fundamentals and common elements of service-oriented architecture, in ensuring information used in the initiative is of high quality through three basic steps approach derived to successfully implement service-oriented architecture with greater agility. Further work would be focusing on binding these two areas; information quality and service-oriented architecture, for enterprises to become enterprise service-oriented architecture-enabled.